Nano-frictional investigation on boundary lubricity of oleic acid, methyl oleate and trimethylolpropane trioleate - Lee, Chiew Tin; Lee, Mei Bao; William Chong, Woei Fong; Syahrullail, Samion (Malaysian Tribology Society, 2022)
Vegetable-oil-based lubricant is one of the alternative resources to overcome environmental contamination of unregulated disposal of fossil-fuel-based lubricants. In this study, boundary lubricity of three different vegetableoil-based lubricants, namely oleic acid, methyl oleate, and trimethylolpropane (TMP) trioleate, are characterised using Lateral Force Microscopy (LFM) with fluid imaging under contact mode. Frictional measurements are conducted using an AFM tip sliding on a stainless-steel substrate at varied applied normal loads (1-10 nN) and AFM tip sliding velocities (2–200 µm/s). The obtained frictional data is further analysed based on Eyring thermal activation energy approach. The coefficient of friction (CoF) values for TMP trioleate are the lowest across the range of sliding velocities, except at 200 µm/s. The boundary friction properties of methyl oleate are shear activated, where the measured CoF reduces significantly with increasing AFM tip sliding velocities. It is also to highlight that methyl oleate produced the lowest CoF at 200 µm/s among the tested fluids. Such a boundary lubricity characteristic could be attributed to a more balanced activation energy property as compared to oleic acid and TMP trioleate, where a stronger boundary fil